Factors Related to Delayed Antiretroviral Therapy Initiation inHIV Patients - NLP, Dwi Rahayu; Karjadi, Teguh H; Nelwan, Erni J (UI Scholars Hub, 2016)
Introduction. Increase access towards antiretroviral therapy (ART) contribute to global decrease of HIV-associated morbidity and mortality. Time to initiation of ART in eligible HIV-infected patients is associated with reduction in mortality and morbidity. Delayed initiation of antiretroviral therapy can lead to increased of mortality rate more than 10% compare to early initiation. Methods. This study was a cross sectional study among adult HIV patients in Out-patient Clinic of HIV Integrated Clinic Cipto Mangunkusumo General Hospital who started ARV therapy for the first time (ART-naïve patients) enrolled from January 2013 to December 2014. The data were extracted from medical records to identify factors associated with delayed initiation ART among HIV patient. Delayed initiation ART was defined as eligible patients didn’t initiate ART within 10 weeks after the diagnosis of HIV infection. Factors identified were gender, education level, employment, marital status, WHO clinical stage, BMI, functional status, and the presence of opportunistic infection. Logistic regression test was used to find factors associated with delayed initiation of ART. Results. There were 444 subjects in this study, which consisted of 107 patients (24.1%) who delayed initiation of ART and 337 patients (75.9%) who didn’t delayed initiation of ART. Based on the bivariate analysis, there were three variables statistically significance, which were advanced WHO clinical stage (p<0.001), lower functional status (p<0.001) and the presence of opportunistic infection (p<0.001). Further multivariate analysis showed that there were two variables associated with delayed initiation of ART, which were advanced WHO clinical stage (OR: 2.92, 95%CI 1.53-7.40, p=0.02) and the presence of opportunistic infection (OR 1.99, 95%CI 1.21-3.29, p=0.01). Conclusions. Advanced WHO clinical stage and the presence of opportunistic infections are factors associated with delayed initiation of ART among HIV patients.